1992
DOI: 10.1111/j.1600-0404.1992.tb05081.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression by whole-body irradiation and its effect on oedema in experimental cerebral ischaemia

Abstract: The effect of global immunosuppression by sublethal whole body X-irradiation on the development of cerebral oedema was assessed 24 h after right middle cerebral artery occlusion in the rat. Irradiation produced a significant leukopenia and thrombocytopaenia, and significantly reduced cortical oedema when compared to non-irradiated control animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In particular, the degree of leukocyte infiltration following focal stroke correlates with the severity of neuronal injury and neurological deficits in animals Clark et al, 1994;del Zoppo et al, 1991) and humans (Akopov et al, 1996). Moreover, in focal ischemia models, anti-leukocyte interventions decrease cerebral edema (Strachan et al, 1992), improve cerebral blood flow (Grogaard et al, 1989;Connolly et al, 1996;Ishikawa et al, 2004), and reduce infarct size (Connolly et al, 1996;Chopp et al, 1994;Beech et al, 2001;Xu et al, 2004;Zheng et al, 2004). Finally, adhesion molecule knockout mice consistently exhibit smaller lesion volumes following focal stroke than their wild-type counterparts (Prestigiacomo et al, 1999;Soriano et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the degree of leukocyte infiltration following focal stroke correlates with the severity of neuronal injury and neurological deficits in animals Clark et al, 1994;del Zoppo et al, 1991) and humans (Akopov et al, 1996). Moreover, in focal ischemia models, anti-leukocyte interventions decrease cerebral edema (Strachan et al, 1992), improve cerebral blood flow (Grogaard et al, 1989;Connolly et al, 1996;Ishikawa et al, 2004), and reduce infarct size (Connolly et al, 1996;Chopp et al, 1994;Beech et al, 2001;Xu et al, 2004;Zheng et al, 2004). Finally, adhesion molecule knockout mice consistently exhibit smaller lesion volumes following focal stroke than their wild-type counterparts (Prestigiacomo et al, 1999;Soriano et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 It has been reported that immunosuppression by sublethal whole body X-irradiation resulted in a significant reduction of brain edema and leukopenia after middle cerebral artery occlusion. 34 Furthermore, leukopenia induced by an anticancer drug has been reported to reduce infarct volumes after transient cerebral ischemia. 29 Although this study did not show that tacrolimus treatment suppressed leukocyte activation, leukocyte accumulation after transient ischemia was significantly ameliorated with tacrolimus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…33 Therefore, it would be very valuable to investigate leukocyte dynamics in the cerebrum after transient ischemia. 10,28,29,34 Unfortunately, only a few techniques allow us to investigate the cerebral microcirculation. [11][12][13] With increased spatial resolution and depth penetration, confocal laser scanning microscopy permits the evaluation of leukocyte dynamics in the microcirculation of the pia mater and the outer layers of the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accumulated leukocytes have been shown to cause tissue injury by producing superoxide radicals (Werns et al, 1985) and various kinds of in¯ammatory cytokines (Ghezzi et al, 1991). Recently, experiments investigating leukocyte adhesion to the vascular endothelium have shown leukocyte recruitment to regions of in¯ammation to be mediated through a multistep process (Bevilacqua and Nelson, 1993), mediated by distinct adhesion molecules and elaborately regulated (Strachan et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Many experimental studies have shown improvement in ischemia-reperfusion injury with reduction of leukocyte participation. Thus immunosuppression by sublethal whole body X-irradiation (Strachan et al, 1992), and leukopenia produced by leukocyte ®ltration or anticancer drugs (Heinel et al, 1994) successfully reduces leukocyte accumulation and tissue damage during ischemia reperfusion injury. Leukocyte±endothelial interactions are regulated by multistep processes (Osborn, 1990), with each step mediated by distinct adhesion molecules (Lawrence and Springer, 1991).…”
Section: Introductionmentioning
confidence: 99%